Study on Influencing Factors Analysis of Gastric Tube Insertion Length and Construction of Estimation Method - Zhang, Hua; Wang, Huaqin; Fan, Xiaoyu; Cao, Xiangqun; Su, Wan; Yang, Bo (Frontiers in Surgery, 2022)
Background. Influenced by individual differences, the depth of gastric tube placement is often different. Clinically, it is necessary to seek a simple and accurate gastric tube insertion scheme to improve the clinical efficacy of indwelling gastric tube. Materials and Methods. A total of 100 adult patients undergoing transesophageal manometry via nose were included in the study. The in vivo length (NCL) of apex-cardia was measured. At the same time, we entered our institutional database, summarized the clinical data of 100 patients, and analyzed the risk factors affecting NCL using stepwise regression analysis. Results. The NCL length scores of patients with different gender, age, marital status, height, weight, BMI, sitting height, sternum length, hairline-xiphoid process, nose tip-earlobe-xiphoid process and earlobe-xiphoid process were statistically significant (P < 0.05). Height, sitting height, gender, BMI and earlobe-xiphoid process were the factors that affected the NCL length score (P < 0.05). The prediction equation of the estimation method of gastric tube insertion length was as follows: NCL length score =39.907+2.909× height +0.865× sitting height. Adjust R2 to 0.506. NCL was positively correlated with height and sitting height. Among them, the correlation with height (r=0.711, P<0.001) and sitting height (r=0.397, P<0.001). Conclusion. Height, sitting height, gender, BMI and earlobe-xiphoid process were the factors that affected the score of NCL length. There was a significant positive correlation between height, sitting height and NCL length. On this basis, the length of nasogastric tube insertion could be estimated.